2013
DOI: 10.1016/s0924-9338(13)75790-0
|View full text |Cite
|
Sign up to set email alerts
|

464 – A prospective study of patients absconding from a psychiatric hospital in Iran

Abstract: Introduction:Absconding from a psychiatric ward (leaving without permission) is a costly event in many ways.Objectives:Some risks of absconding include missed treatment which results in longer rehabilitation time or lack of treatment altogether.Aim:To investigate the motivation and characteristics of patients absconding from a psychiatric ward in Iran.Methods:A prospective study was conducted for patients who absconded from psychiatric ward in the period between July 2010 and July 2011. The variables were pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…The rate of absconding in this hospital was low (0.50%), which was similar to studies conducted in other general hospitals (0.30%) (12). These rates are significantly lower than psychiatric hospitals or psychiatric wards (5,12,13). For example, the absconding rate was reported about 13.33% in psychiatric wards in Australia (14) and 14.21% in India (a non-industrial country) (15).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The rate of absconding in this hospital was low (0.50%), which was similar to studies conducted in other general hospitals (0.30%) (12). These rates are significantly lower than psychiatric hospitals or psychiatric wards (5,12,13). For example, the absconding rate was reported about 13.33% in psychiatric wards in Australia (14) and 14.21% in India (a non-industrial country) (15).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, some cases in the United States have been described that subsistence expenditure was the main cause of absconding (10). Some studies conducted in psychiatric hospitals in Iran have revealed that risk of absconding is higher in male and single patients (6) and in the early days of admission (5). However, we were unable to find research regarding the absconding from general hospital and the characteristics of absconders in Iran.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The authors carried out a study about patients absconding from Zare hospital. In that study we found absconding was more frequent in summer ( Sheikhmoonesi, Kabirzadeh, Yahyavi, & Mohseni, 2012 ).…”
Section: Discussionmentioning
confidence: 64%
“…For others, absconding was reflective of goal-directed behavior, either to complete a task (e.g., related to household responsibilities) or to obtain substances. A recent study of psychiatric patients who absconded in Iran found similar motivational themes, including feelings of boredom as well as missing family members [ 15 ]. Few studies have found evidence of symptom-driven motivation when patients are asked directly about their reasons for absconding (e.g., [ 14 ]); however, fear and safety concerns were noted to play a significant role in patients’ decisions to abscond, as were failures in the therapeutic relationship with staff [ 16 ].…”
Section: Introductionmentioning
confidence: 99%